Specification for general purpose rubber water hoses (BSI, 1980)
Flexible pipes, Water, Natural rubber, Synthetic rubber, Reinforced materials, Diameter, Thickness, Length, Dimensional tolerances, Tensile strength, Elongation at fracture, Ageing (materials), Adhesive strength, Marking, Service pressure, Pressure